New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)
fs-ref-orig: Benoit, J., Dagnogo, D.S., Savard, J., & Savard, S. (2021, mise à jour 2025). Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html. fs-code-orig: Benoit-2025c

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Protocole d’évaluation de la sécurité à domicile (PESAD) : version francophone du SAFER-HOME v.3 - Hébert, Michèle; Brasset-Latulippe, Anne; Bourgault-Côté, Sylvianne; Meilleur, Valérie; Chiu, Teresa (Francophonies d'Amérique, 2009)
Les intervenants de la santé sont appelés à se prononcer sur la sécurité des aînés vivant à domicile et ils ont, à cet effet, très peu d’outils francophones à leur disposition. Le Protocole d’évaluation de la sécurité à domicile (PESAD) est issu de la traduction et de la validation transculturelle du SAFER-HOME. Le processus de validation et l’étude de la fidélité des résultats ont mis en lumière un outil intéressant et possédant de bonnes qualités métrologiques. Il permet aux intervenants francophones d’obtenir des résultats d’évaluation complets et rigoureux relativement à la sécurité à domicile des aînés francophones.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Évaluation métrologique de la Mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Benoît, Josée; Bouchard, Pier (Reflets, 2014)
Comment peut-on mesurer l’impact des actions entreprises pour améliorer l’offre active de services sociaux et de santé en français dans les communautés francophones en situation minoritaire? Un questionnaire mesurant premièrement les comportements individuels de l’offre active et deuxièmement la perception du soutien organisationnel à faire de l’offre active a été créé. La validité de contenu de la Mesure de l’offre active de services en françaisen contexte minoritaire a été établie à l’aide d’une recension d’écrits, de consultations menées auprès d’expertes et d’experts et d’un sondage Delphi pancanadien. Sa fidélité a été examinée à partir de données recueillies auprès de récents diplômés en santé et en service social. L’outil démontre une bonne consistance interne et des études auprès d’un plus large échantillon sont nécessaires pour augmenter la confiance envers sa stabilité temporelle. Il s’agit des premiers pas d’une démarche visant à mesurer l’évolution des comportements d’offre active à la suite d’activités de formation ou de changements organisationnels en faveur de services en français. Une telle mesure est aussi susceptible d’être utile dans les recherches visant à saisir les déterminants de ces comportements d’offre active. Mots-clés : Offre active de services en français, formation des professionnelles ou professionnels en santé et services sociaux, soutien organisationnel, évaluation, minorité, langue et services, qualité des soins et services, sécurité des clientes ou clients/patientes ou patients

Behaviours demonstrating active offer: Identification, measurement, and determinants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Les comportements favorables à l’offre active, leur mesure et leurs déterminants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, nous présenterons comment nous avons répertorié des comportements favorables à une offre active (OA) de services sociaux et de santé en français en contexte minoritaire, comment nous les avons mesurés et comment nous avons utilisé ces mesures pour déceler des déterminants de l’OA. Nous présentons en détail l’élaboration des outils qui ont servi à mesurer les comportements d’OA, le soutien organisationnel perçu envers l’OA et les caractéristiques personnelles qui peuvent influer sur les comportements d’OA (déterminants). Diverses méthodes quantitatives ont été utilisées pour atteindre ces objectifs. Les résultats obtenus démontrent la présence d’un fort lien entre le soutien organisationnel perçu et les comportements individuels d’OA. À soutien organisationnel égal, les caractéristiques individuelles associées à une plus grande propension à démontrer des comportements d’OA incluent une formation sur l’OA, l’affirmation identitaire et la compétence en français. Le sentiment de compétence en anglais est quant à lui associé négativement aux comportements individuels d’OA de services en français. Une meilleure connaissance de ces déterminants permet de raffiner les stratégies de sensibilisation et d’éducation des futurs professionnels de la santé et des services sociaux envers l’OA. Mots-clés : comportements d’offre active, mesure, déterminants, soutien organisationnel, comportements individuels, recherche quantitative.
Chapitre 12

La thérapie informatisée : une option pouvant faciliter l'accès à la thérapie chez les jeunes adultes ? - Talbot, France; LeBlanc, Josée; Jbilou, Jalila (Santé mentale au Quebec, 2015)
Introduction Les jeunes adultes ont, au Canada, les plus hauts taux de prévalence de l’anxiété et de la dépression, et sont aussi ceux qui utilisent le moins les services traditionnels de santé mentale. Faciliter l’accès à la thérapie chez les jeunes est ainsi particulièrement important, et ce, encore davantage dans les régions canadiennes plus rurales et auprès des minorités linguistiques. La thérapie informatisée pourrait être une option. Objectifs Cette étude vise à évaluer jusqu’à quel point l’autostigmatisation, un besoin d’autonomie et les attitudes face à la thérapie informatisée permettent de prédire l’intention d’utiliser cette thérapie chez de jeunes adultes francophones. L’impact de la visite du site Web d’une clinique virtuelle sur cette intention a également été évalué. Méthode Quarante-quatre étudiants fréquentant une université francophone du Nouveau-Brunswick ont complété, en ligne, des mesures autorapportées avant et suite à la visite du site Web de la clinique virtuelle MindSpot, en Australie, qui offre des thérapies informatisées. Résultats Une séquence de corrélations significatives entre les variables étudiées est observée, mais seules des attitudes plus positives à l’égard de la thérapie informatisée sont directement corrélées à une plus grande intention de l’utiliser. La visite du site Web a produit une augmentation significative et importante de l’intention d’utiliser la thérapie informatisée. Conclusions La thérapie informatisée pourrait faciliter l’accès aux traitements fondés sur les données probantes du stress, de l’anxiété et de la dépression chez les jeunes adultes francophones du Nouveau-Brunswick, voir d’autres parties du Canada. Cette approche demeure peu répandue encore à travers le pays. Mots-clés : thérapie autogérée, thérapie informatisée, jeunes adultes, anxiété, dépression, attitudes